2019
DOI: 10.1038/s41598-019-42115-y
|View full text |Cite
|
Sign up to set email alerts
|

Functional evaluation of PDGFB-variants in idiopathic basal ganglia calcification, using patient-derived iPS cells

Abstract: Causative genes in patients with idiopathic basal ganglia calcification (IBGC) (also called primary familial brain calcification (PFBC)) have been reported in the past several years. In this study, we surveyed the clinical and neuroimaging data of 70 sporadic patients and 16 families (86 unrelated probands in total) in Japan, and studied variants of PDGFB gene in the patients. Variant analyses of PDGFB showed four novel pathogenic variants, namely, two splice site … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 41 publications
0
20
0
Order By: Relevance
“…IBGC is characterized by abnormal mineral deposits, mostly calcium, in brain regions, including the basal ganglia, thalamus, cerebellum, and others. We have investigated the patients in Japan 4,5 . We have 231 patients with 33 familial case now in Japan.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…IBGC is characterized by abnormal mineral deposits, mostly calcium, in brain regions, including the basal ganglia, thalamus, cerebellum, and others. We have investigated the patients in Japan 4,5 . We have 231 patients with 33 familial case now in Japan.…”
Section: Introductionmentioning
confidence: 99%
“…Most recently, MYORG is identified as a new causative gene of IBGC and is associated with recessive IBGC 10 . Among these, IBGC1 is the most frequent and accounts for about 30%–50% of familial cases 2,4,5 . Currently, no effective therapy is available for patients with IBGC 2 .…”
Section: Introductionmentioning
confidence: 99%
“…As of the end of January 2021, according to the Human Gene Mutation Database (HGMD, www.hgmd.cf.ac.uk/ac/index.php), 142 mutations in SLC20A2 have been identified, including 75 missense and non-sense mutations, 15 splice-site mutations, 32 small deletions, 5 small insertions and duplications, and 15 gross mutations; 24 mutations were identified in PDGFB, including 19 missense and non-sense mutations, three splice-site mutations, and two gross deletions. We summarized and compiled the other four pathogenic mutations in PDGFB from the literature (Sekine et al, 2019). In the present study, we identified two novel frameshift mutations in SLC20A2 (c.806delC and c.1154delG) and one splice donor site mutation in PDGFB (c.456+1G>C), which have broadened and enriched the SLC20A2 and PDGFB mutation spectrum (Supplementary Figure 2).…”
Section: Discussionmentioning
confidence: 85%
“…However, both patients in the nuclear family had a severe migraine, a history of depression, and calcification in the basal ganglia, thalamus (only mother affected), cerebral cortex (only proband affected), and subcortical white matter (Ramos et al, 2018). Another splice acceptor site mutation in the same intron (c.457-1G>T) may lead to exon 5 (NM_002608.4) skipping and frameshift protein in carriers, leading to chronic headache and intellectual disability (Sekine et al, 2019). These results suggest that different substitutions on the same splicing unit (GT-AG in DNA code) could result in distinct molecular events and disease phenotypes.…”
Section: Discussion Clinical Phenotype Genetic Heterogeneity and Genetic Complexity In Brain Calcificationmentioning
confidence: 99%
See 1 more Smart Citation